Influence of Dopant Type and Orientation of Silicon Anodes on Performance, Efficiency and Corrosion of Silicon–Air Cells with EMIm(HF)2.3F Electrolyte. Issue 12 (5th August 2017) - Durmus, Yasin Emre; Jakobi, Simon; Beuse, Thomas; Aslanbas, Özgür; Tempel, Hermann; Hausen, Florian; de Haart, L. G. J.; Ein-Eli, Yair; Eichel, Rüdiger-A.; Kungl, Hans
Abstract : Intermediate term discharge experiments were performed for Si–air full cells using As-, Sb- and B-doped Si-wafer anodes, with 〈100〉 and 〈111〉 orientations for each type. Discharge characteristics were analyzed in the range of 0.05 to 0.5 mA/cm 2 during 20 h runs, corrosion rates were determined via the mass-change method and surface morphologies after discharge were observed by laser scanning microscopy and atomic force microscopy. Corresponding to these experiments, potentiodynamic polarization curves were recorded and analyzed with respect to current-potential characteristics and corrosion rates. Both, discharge and potentiodynamic experiments, confirmed that the most pronounced influence of potentials – and thus on performance – results from the dopant type. Most important, the corrosion rates calculated from the potentiodynamic experiments severely underestimate the fraction of anode material consumed in reactions that do not contribute to the conversion of anode mass to electrical energy. With respect to materials selection, the estimates of performance from intermediate term discharge and polarization experiments lead to the same conclusions, favoring 〈100〉 and 〈111〉 As-doped Si-wafer anodes. However, the losses in the 〈111〉 As-doped Si-anodes are by 20% lower, so considering the mass conversion efficiency this type of anode is most suitable for application in non-aqueous Si–air batteries.